OPTIMIZATION STRATEGY FOR CARBON TAX IN SUPPORTING THE 2060 NET ZERO EMISSION TARGET - Angelo Fernando; Andreas Bambang Daryatno (Jurnal Apresiasi Ekonomi, 2026)
This study analyzes the role of the carbon tax as an environmental fiscal policy instrument in supporting Indonesia’s Net Zero Emission (NZE) 2060 target. The carbon tax functions not only as a source of state revenue but also as an emission control tool encouraging industries to adopt cleaner energy. Using a qualitative descriptive and evaluative approach, the study reviews literature, government regulations, and corporate sustainability reports. The findings reveal that implementation challenges persist, including industrial readiness, emission monitoring systems, and policy coordination. However, with progressive tax rates, revenue allocation for renewable energy, and just transition mechanisms, the carbon tax can effectively support sustainable development. The study concludes that a well-designed and equitable carbon tax policy can strengthen Indonesia’s transition toward a low-carbon economy and the NZE 2060 goal